2012
DOI: 10.1016/j.jeurceramsoc.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the eutectic temperature in air of the CuO–TiO2 pseudobinary system

Abstract: Eutectic temperature and composition in the CuO-Ti0 2 pseudobinary system have been experimentally determined in air by means differential thermal analysis (DTA), thermogravimetry (TG) and hot-stage microscopy (HSM). Samples of the new eutectic composition treated at different temperatures have been characterized by X-ray diffraction (XRD) and X-ray absorption near-edge structural spectroscopy (XANES) to identify phases and to determine the Cu valence state, respectively. The results show that the eutectic tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
9
14
0
Order By: Relevance
“…The current study measured the eutectic temperature of the TiO 2 -CuO system to be 1010 ± 10 C in air, which was higher than that reported in 2001 [14], but similar to that suggested by a DSC and TG study in 2012 [15]. This warrantees our re-assessment and a correction of the TiO 2 -CuO phase diagram reported in Ref.…”
Section: Further Discussion Of Activated Sintering Mechanisms and Beyondsupporting
confidence: 89%
See 3 more Smart Citations
“…The current study measured the eutectic temperature of the TiO 2 -CuO system to be 1010 ± 10 C in air, which was higher than that reported in 2001 [14], but similar to that suggested by a DSC and TG study in 2012 [15]. This warrantees our re-assessment and a correction of the TiO 2 -CuO phase diagram reported in Ref.…”
Section: Further Discussion Of Activated Sintering Mechanisms and Beyondsupporting
confidence: 89%
“…That diagram reported in 2001 [14] represents the only TiO 2 -CuO phase diagram available in literature and has been widely cited. The more accurate measurements of the eutectic temperature and composition obtained in this study, which were consistent with the independent DSC/TG study in 2012 [15], demand a further assessment (and correction) of that TiO 2 -CuO phase diagram, which will also provide the thermodynamic function of the liquid phase that will be useful for the interfacial thermodynamic model presented and discussed in the following section.…”
Section: The Tio 2 -Cuo Binary Phase Diagram and Bulk Thermodynamic Fsupporting
confidence: 84%
See 2 more Smart Citations
“…4). Rubia et al [20] reported a eutectic melting point for this composition at about 1000 °C and it seems likely that the formation of the large coarse grains may be the result of a liquid-phase sintering mechanism. The Cu-rich small grains and intergranular phase observed in the FE-SEM images (Fig.…”
Section: Compositionmentioning
confidence: 81%